Aliphatic polyesters, polyester compositions containing the same, and their use
Patent Information
- Application Number
- JP2026037604
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-10
- Filing Date
- 2026-03-10
- Publication Date
- 2026-10-30
AI Technical Summary
Aliphatic polyesters exhibit low heat seal strength, leading to issues such as packaging bag edges bursting or bottoms penetrating during use, which affects production efficiency and quality.
The development of an aliphatic polyester with controlled mole fractions of succinic and sebacic acid residues and the incorporation of a branching agent within specific ranges to form a branched structure, lowering the melting point and enhancing heat seal strength.
The resulting aliphatic polyester achieves high heat seal strength, preventing bag failures and improving production efficiency while maintaining mechanical properties and degradability.
Abstract
Description
[Technical Field]
[0001] The present invention relates to the technical field of polyester materials, and specifically to an aliphatic polyester, a polyester composition comprising the same, and uses thereof. [Background Art]
[0002] Biodegradable polyesters obtained from dicarboxylic acids and diols are not only biodegradable, but also have excellent elongation and certain mechanical properties, and have properties similar to low-density polyethylene (LDPE) and linear low-density polyethylene (LLDPE). Therefore, they are widely used in packaging bags such as shopping bags, courier bags, and fruit and vegetable bags.
[0003] Packaging bags usually require heat sealing treatment during processing to meet usage requirements. The quality of heat sealing directly affects whether the edge of the packaging bag will burst or the bottom will penetrate during use. Heat sealing strength is an important indicator for evaluating heat sealing quality. Heat sealing strength is not only affected by the heat sealing process (heat sealing time, temperature, pressure), but also related to the structure of the material itself. Aliphatic-aromatic polyesters such as polybutylene adipate terephthalate (PBAT) have relatively good mechanical properties, but the presence of aromatic dicarboxylic acid ester segments may deteriorate the degradability of the polyester material. Meanwhile, the melting point of the polyester is relatively high. Due to the relatively high melting point, a relatively high heat sealing temperature (usually above 135°C) is required during heat sealing. However, if the heat sealing temperature is too high, the diffusion of molecular chains of the material will be accelerated, and in a relatively short heat sealing time, the entanglement of molecular chains between interfaces is limited, resulting in a decrease in heat sealing strength. On the other hand, if the temperature is too high, the material will undergo a certain degree of thermal decomposition during the heat sealing process, which further reduces the heat sealing strength.
[0004] Aliphatic polyesters such as polybutylene succinate sebacate have good biodegradability, lack aromatic structures, and have low melting points, thus eliminating the need for high heat sealing temperatures and avoiding the effect of heat sealing temperature on heat seal strength. However, the heat seal strength of aliphatic polyesters themselves is relatively low, which affects the performance and production efficiency of packaging bags.
[0005] Therefore, the development of aliphatic polyesters with high heat-seal strength has become an urgent issue to be addressed in this field. [Overview of the project] [Problems that the invention aims to solve]
[0006] The present invention aims to provide aliphatic polyesters, polyester compositions containing them, and their use, in order to overcome the shortcomings of the prior art. The aliphatic polyester solves the problem in the prior art where the edges of packaging bags burst or the bottom is penetrated due to the low heat seal strength of aliphatic polyesters. [Means for solving the problem]
[0007] To achieve this objective, the present invention employs the following technical solutions.
[0008] In a first aspect, the present invention provides an aliphatic polyester comprising a dibasic acid residue, a diol residue, and a branching agent residue, wherein the dibasic acid residue comprises, as residues, a1): 71-89 mol% succinic acid residues based on a total mole fraction of 100 mol% of a1) and a2), and a2): 11-29 mol% sebaciate residues based on a total mole fraction of 100 mol% of a1) and a2), the diol residue is selected from at least an equimolar amount of 1,4-butanediol residues with respect to the dibasic acid residue, the branching agent residue is derived from a branching agent with ≥3 self-functional groups, and the mass fraction of the branching agent residue is 0.09-0.22 wt% when the total mass of the aliphatic polyester is 100 wt%.
[0009] In this invention, by controlling the mole fractions of succinic acid residues and sebacic acid residues within a specific range, the melting point of the aliphatic polyester can be lowered (to less than 100°C) while ensuring the mechanical properties, heat resistance, and degradability of the aliphatic polyester, thereby lowering the heat seal temperature and improving heat seal strength. By incorporating branching agent residues and controlling the amount of branching agent residues within a specific range, an aliphatic polyester having a specific branched structure can be formed, further improving the heat seal strength of the aliphatic polyester. As a result, packaging bags containing the aliphatic polyester have high heat seal strength, avoiding problems such as the edges of the packaging bags bursting or the bottom being penetrated, and improving production efficiency.
[0010] The term "residue" refers to any organic structure introduced into the polymer molecular chain by related monomers through polycondensation reactions, i.e., an organic structure derived from related monomers. For example, a dibasic acid residue refers to a structure derived from a dibasic acid monomer in an aliphatic polyester.
[0011] In this invention, succinic acid and / or succinic acid derivatives are introduced into the molecular chains of polyester through a polymerization reaction to form succinic acid residues. Sebacic acid and / or sebacic acid derivatives are introduced into the molecular chains of polyester through a polymerization reaction to form sebacic acid residues. If the succinic acid residue content is too low or too high, the crystallization rate is slow, the strength is low, and the heat resistance is poor. If the succinic acid residue content is too high or too low, the melting point is high, the heat seal temperature is high, and the decomposition rate is poor.
[0012] In the present invention, the succinic acid derivative includes an alkyl succinate, and exemplary the alkyl succinate may be at least one of dimethyl succinate, diethyl succinate, di-n-propyl succinate, diisopropyl succinate, di-n-butyl succinate, diisobutyl succinate, di-tert-butyl succinate, di-n-pentyl succinate, diisopentyl succinate, and di-n-hexyl succinate. The alkyl succinate may be an alkyl ester formed from succinic acid, or an alkyl ester formed from succinic anhydride, and preferably dimethyl succinate formed using succinic anhydride.
[0013] In the present invention, the sebacate derivative comprises an alkyl sebacate, and exemplary the alkyl sebacate may be at least one of dimethyl sebacate, diethyl sebacate, di-n-propyl sebacate, diisopropyl sebacate, di-n-butyl sebacate, diisobutyl sebacate, di-tert-butyl sebacate, di-n-pentyl sebacate, diisopentyl sebacate, or di-n-hexyl sebacate. The alkyl sebacate may be an alkyl ester formed from sebacate or an alkyl ester formed from sebacate anhydride.
[0014] Preferably, the dibasic acid residue comprises, as a residue, 74-83 mol% succinic acid residues based on a total mole fraction of 100 mol% of a1): a1) and a2), and 17-26 mol% sebacic acid residues based on a total mole fraction of 100 mol% of a2): a1) and a2), and more preferably, 74-80 mol% succinic acid residues based on a total mole fraction of 100 mol% of a1): a1) and a2), and 20-26 mol% sebacic acid residues based on a total mole fraction of 100 mol% of a2): a1) and a2).
[0015] In the present invention, the mass fraction of the branching agent residue is 0.09 to 0.22 wt%, for example, 0.09 wt%, 0.092 wt%, 0.094 wt%, 0.098 wt%, 0.1 wt%, 0.102 wt%, 0.104 wt%, 0.106 wt%, 0.108 wt%, 0.11 wt%, 0.112 wt%, 0.114 wt%, 0.116 wt%, 0. 118wt%, 0.12wt%, 0.122wt%, 0.124wt%, 0.126wt%, 0.128wt%, 0.13wt%, 0.132wt%, 0.134wt%, 0 .136wt%, 0.138wt%, 0.14wt%, 0.142wt%, 0.144wt%, 0.146wt%, 0.148wt%, 0.15wt%, 0.152wt%, 0.154wt%, 0.156wt%, 0.158wt%, 0.16wt%, 0.162wt%, 0.164wt%, 0.166wt%, 0.168wt%, 0.17wt% , 0.172wt%, 0.175wt%, 0.178wt%, 0.18wt%, 0.182wt%, 0.185wt%, 0.188wt%, 0.19wt%, 0.192wt The mass of the branching agent residue may be %, 0.195 wt%, 0.198 wt%, 0.2 wt%, 0.202 wt%, 0.205 wt%, 0.208 wt%, 0.21 wt%, 0.212 wt%, 0.215 wt%, 0.218 wt%, 0.22 wt%, or within any of the above values, but preferably the mass of the branching agent residue is 0.11 to 0.17 wt%.
[0016] In the aliphatic polyester of the present invention, the content of branching agent residues can be tested by liquid chromatography-mass spectrometry (LC-MS).
[0017] In this invention, the structure of an aliphatic polyester is converted from a linear polyester to a branched polyester by adding a polyfunctional branching agent. As the amount of branching agent added increases, the number of molecules with long and short branches in the molecular segment increases, making it easier for entanglement between interfaces to occur during heat sealing, and improving the heat seal strength. However, if too much branching agent is added, the crystallization rate of the polyester increases significantly, and the degree of crystallinity increases. When the degree of crystallinity increases, the energy required to melt the material and complete the heat seal during the heat sealing process increases. Therefore, if the branching agent content is too high, the heat seal strength may decrease.
[0018] Preferably, the molecular structure of the branching agent includes at least one of hydroxy, carboxy, or acid anhydride.
[0019] Preferably, the branching agent comprises at least one of a polyol, a polybasic acid, a polyolic acid, or a polybasic acid anhydride, and more preferably a polyol.
[0020] Preferably, the polyol comprises at least one of trimethylolpropane, trimethylolethane, pentaerythritol, polyethertriol, or glycerin.
[0021] Preferably, the polybasic acid includes at least one of trimesic acid, trimellitic acid, or pyromellitic acid.
[0022] Preferably, the polyol acid comprises at least one of tartaric acid, citric acid, or malic acid.
[0023] In this invention, the polyol acid refers to one whose molecular structure contains at least one hydroxyl group and at least one carboxyl group.
[0024] Preferably, the polybasic acid anhydride includes trimellitic anhydride and / or pyromellitic dianhydride.
[0025] Preferably, the molecular weight distribution coefficient of said aliphatic polyester is 1.3 to 2.8, for example, it may be 1.3, 1.4, 1.5, 1.52, 1.54, 1.56, 1.58, 1.6, 1.62, 1.64, 1.66, 1.68, 1.7, 1.72, 1.74, 1.76, 1.78, 1.8, 1.82, 1.84, 1.86, 1.88, 1.9, 1.92, 1.94, 1.96, 1.98, 2, 2.1, 2.15, 2.2, 2.25, 2.3, 2.35, 2.4, 2.45, 2.5, 2.6, 2.7, 2.8, or a range between any of the above numerical values, and more preferably 1.5 to 2.5.
[0026] In the present invention, the molecular weight distribution coefficient is the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn), which can be obtained by testing Mw and Mn via gel permeation chromatography and calculation. The branching agent and its content affect the molecular weight distribution coefficient: when the content of the branching agent increases, the molecular weight distribution coefficient of the polyester broadens. Furthermore, the ratio of alcohol to acid and polymerization conditions (such as temperature, time, pressure, etc.) also affect the molecular weight distribution coefficient.
[0027] Preferably, under the conditions of 190°C and 2.16 kg, the melt flow rate of the aliphatic polyester is 1.2~10 g / 10min, for example, it may be 1.2 g / 10min, 1.4 g / 10min, 1.6 g / 10min, 1.8 g / 10min, 2 g / 10min, 2.2 g / 10min, 2.4 g / 10min, 2.6 g / 10min, 2.8 g / 10min, 3 g / 10min, 3.2 g / 10min, 3.4 g / 10min, 3.6 g / 10min, 3.8 g / 10min, 4 g / 10min, 4.2 g / 10min, 4.4 g / 10min, 4.6 g / 10min, 4.8 g / 10min, 5 g / 10min, 5.2 g / 10min, 5.4 g / 10min, 5.6 g / 10min, 5.8 g / 10min, 6 g / 10min, 6.2 g / 10min, 6.5 g / 10min, 6.8 g / 10min, 7 g / 10min, 7.2 g / 10min, 7.5 g / 10min, 7.8 g / 10min, 8 g / 10min, 8.2 g / 10min, 8.5 g / 10min, 8.8 g / 10min, 9 g / 10min, 9.2 g / 10min, 9.5 g / 10min, 9.8 g / 10min, 10 g / 10min, or a range between any of the above values; more preferably, the melt flow rate is 2.2~6 g / 10min.
[0028] In the present invention, the melt flow rate is tested in accordance with the standard ISO 1133-2-2012, and the test conditions are 190°C and 2.16 kg.
[0029] In the present invention, in consideration of hydrolysis resistance, aging resistance, biodegradation resistance and cost, the carboxyl content of the aliphatic polyester is preferably <50 mol / t, more preferably <30 mol / t, particularly preferably <15 mol / t.
[0030] In the present invention, the carboxyl content is tested in accordance with GB / T 32366-2015. The carboxyl content can be controlled by changing conditions such as the ratio of alcohol to acid, polymerization temperature and polymerization time, and can also be controlled by suppressing the type and amount of impurities in raw materials such as nitrogen compounds and metal ions.
[0031] In the present invention, the method for producing the aliphatic polyester is not particularly limited, and it is sufficient as long as an aliphatic polyester having a specific branched structure of the present invention can be produced. Preferably, the method for producing the aliphatic polyester is Step (1) involves reacting a dibasic acid, a diol, and a branching agent to obtain an esterification product, Step (2) involves subjecting the esterification product obtained in step (1) to a prepolymerization reaction to obtain a prepolymerization product, The process includes step (3), in which the prepolymerization product obtained in step (2) is subjected to a polycondensation reaction to obtain the aliphatic polyester.
[0032] In the present invention, the dibasic acid may be used alone or as a mixture of at least two types.
[0033] In the present invention, the molar ratio of the diol to the dibasic acid is (1.2 to 3):1, and may be, for example, 1.2:1, 1.5:1, 1.8:1, 2:1, 2.2:1, 2.5:1, 2.8:1, 3:1, or any of the above values, but more preferably (1.4 to 2):1.
[0034] In the present invention, the reaction in step (1) includes an esterification reaction and / or a transesterification reaction. The reaction is carried out at a temperature of 150 to 220°C, a pressure of 0.7 to 1.2 bar, and for a duration of 2 to 7 hours, and more preferably at a temperature of 158 to 215°C, a pressure of 0.75 to 1.15 bar, and for a duration of 2.5 to 6 hours.
[0035] In the present invention, step (1) may be carried out in a single mixing apparatus, in which a dibasic acid, a diol, and a branching agent are mixed to obtain a reaction material mixture, and then the temperature is raised to allow the reaction to proceed.
[0036] In the present invention, the carboxyl content of the esterification product in step (1) is ≤350 mol / t.
[0037] In this invention, after the reaction in step (1), the present invention further includes a step of removing excess diol by distillation, and the removed diol can be recycled as a raw material after purification by distillation. The purity of the purified diol is ≥95%.
[0038] In the present invention, the preliminary polymerization reaction in step (2) is carried out at a temperature of 230 to 260°C, a pressure of 0.3 to 0.8 bar, and for a duration of 70 to 200 mins, and more preferably, the reaction is carried out at a temperature of 235 to 245°C, a pressure of 0.4 to 0.75 bar, and for a duration of 78 to 130 mins.
[0039] In the present invention, step (2) may be carried out in a single prepolymerization reactor.
[0040] In the present invention, the carboxyl content of the prepolymerization product in step (2) is ≤80 mol / t.
[0041] In the present invention, step (3) the polycondensation reaction is carried out at a temperature of 230 to 260°C, a pressure of 0.2 to 5 mbar, and a time of 35 to 120 min, and more preferably, the reaction is carried out at a temperature of 238 to 255°C, a pressure of 0.45 to 3 mbar, and a time of 40 to 115 min.
[0042] In the present invention, step (3) can be carried out in a finishing apparatus suitable for polycondensation reactions, such as a rotary reactor, a cage reactor, or a horizontal reactor.
[0043] In the present invention, the reaction in step (2) is carried out in the presence of a catalyst. The catalyst may be a tin compound, an antimony compound, a cobalt compound, a lead compound, a zinc compound, an aluminum compound, or a titanium compound, but more preferably a zinc compound, an aluminum compound, or a titanium compound, and most preferably a titanium compound. The titanium compound may be tetrabutyl titanate or tetraisopropyl titanate. Compared to other compounds, titanium compounds have lower residue levels in the product and downstream products, and are also less toxic. They are particularly suitable for the production of biodegradable polyesters and can be directly introduced into the environment in the form of compost bags or coating films.
[0044] In this invention, the total mass of the dibasic acid, diol, and branching agent is 100 wt%, and the total mass of the catalyst is 0.001 to 1 wt%.
[0045] In this invention, other auxiliary agents may be added during the reaction in step (3) depending on the actual needs. These other auxiliary agents include, but are not limited to, catalyst passivators.
[0046] The catalyst passivator includes, but is not limited to, a phosphorus compound. The phosphorus compound includes, but is not limited to, one or more of phosphorous acid and phosphoric acid. With a prepolymerization product mass of 100 wt%, the mass of the catalyst passivator is 0.001 to 0.1 wt%, preferably 0.01 to 0.05 wt%. Exemplarily, when a highly active titanium compound is used as the catalyst, a catalyst passivator can be added. Here, the molar ratio of Ti to P is (1.1 to 1.5):1, and particularly preferably, the molar ratio of Ti to P is (1.1 to 1.3):1.
[0047] The present invention further includes a chain extension reaction in which, after the polycondensation reaction, the product obtained by the polycondensation reaction (polycondensation product) is reacted with a chain extender to obtain the aliphatic polyester.
[0048] In the present invention, the chain extender comprises one or more of the following: isocyanate, peroxide, epoxide, oxazoline, oxazine, caprolactam, or carbodiimide.
[0049] In the present invention, the isocyanate may be an aromatic diisocyanate and / or an aliphatic diisocyanate, and the aromatic diisocyanate may be toluene 2,4-diisocyanate, toluene 2,6-diisocyanate, diphenylmethane 2,2'-diisocyanate, diphenylmethane 2,4'-diisocyanate, diphenylmethane 4,4'-diisocyanate, 1,5-naphthalene diisocyanate, or xylene diisocyanate, but particularly preferably diphenylmethane 2,2'-diisocyanate, diphenylmethane 2,4'-diisocyanate, or diphenylmethane 4,4'-diisocyanate. The aromatic diisocyanate may be a polynuclear aromatic diisocyanate, for example, tris(4-isocyanatophenyl)methane having three rings, which can be formed when producing a diisocyanate having one or two rings. The aliphatic diisocyanate may be a linear or branched alkylene diisocyanate having 2 to 20 carbon atoms, or a cycloalkylene diisocyanate having 3 to 20 carbon atoms. Exemplarily, the aliphatic diisocyanate includes hexamethylene diisocyanate, pentamethylene diisocyanate, isophorone diisocyanate, or methylenebis(4-isocyanetocyclohexane) diisocyanate. Hexamethylene diisocyanate is particularly preferred.
[0050] In the present invention, based on the total mass of the polycondensation product, the mass of the isocyanate may be 0.05 to 2 wt%, but is particularly preferably 0.1 to 1.5 wt%.
[0051] In the present invention, the peroxide may be one or more of the following: benzoyl peroxide, 1,1-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di(tert-butylperoxy)methylcyclododecane, n-butylbis(4,4-tert-butylperoxy)valerate, dicumyl peroxide, tert-butylperoxybenzoate, dibutyl peroxide, α,α-di(tert-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexa-3-yne, or tert-butylcumeneperoxide.
[0052] In the present invention, based on the total mass of the polycondensation product, the mass of the peroxide may be 0.1 to 2 wt%, but is particularly preferably 0.2 to 1 wt%.
[0053] In the present invention, the epoxide may be one or more copolymers containing epoxy groups based on diglycidyl ether, hexamethylene diglycidyl ether, sorbitol diglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, resorcinol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and polybutylene glycol diglycidyl ether, styrene, acrylate and / or methacrylate.
[0054] In this invention, based on the total mass of the polycondensation product, the mass of the epoxide may be 0.1 to 2 wt%, but is preferably 0.2 to 1 wt%.
[0055] In the present invention, the oxazoline may be one or more selected from 2,2'-bis(2-oxazoline), bis(2-oxazolinyl)methane, 1,2-bis(2-oxazolinyl)ethane, 1,3-bis(2-oxazolinyl)propane, 1,4-bis(2-oxazolinyl)butane, 1,4-bis(2-oxazolinyl)benzene, 1,2-bis(2-oxazolinyl)benzene, or 1,3-bis(2-oxazolinyl)benzene. The oxazine may be one or more selected from 2,2'-bis(2-dioxazine), bis(2-dioxazinyl)methane, 1,2-bis(2-dioxazinyl)ethane, 1,3-bis(2-dioxazinyl)propane, 1,4-bis(2-dioxazinyl)butane, 1,4-bis(2-dioxazinyl)benzene, 1,2-bis(2-dioxazinyl)benzene, or 1,3-bis(2-dioxazinyl)benzene. The carbodiimide may be one or more selected from N,N'-di-2,6-diisopropylphenylcarbodiimide, N,N'-di-o-tolylcarbodiimide, N,N'-diphenylcarbodiimide, N,N'-dioctyldecylcarbodiimide, N,N'-di-2,6-dimethylphenylcarbodiimide, N-tolyl-N'-cyclohexylcarbodiimide, N,N'-di-2,6-di-tert-butylphenylcarbodiimide, N,N'-di-2,4,6-triisobutylphenylcarbodiimide, diisopropylcarbodiimide, dimethylcarbodiimide, diisobutylcarbodiimide, dioctylcarbodiimide, tert-butylisopropylcarbodiimide, di-β-naphthylcarbodiimide, or di-tert-butylcarbodiimide.
[0056] In the present invention, based on the total mass of the polycondensation product, the masses of oxazoline, oxazine, caprolactam, and carbodiimide are each independently 0.1 to 2 wt%, preferably 0.2 to 1 wt%.
[0057] In this invention, the temperature of the chain extension reaction is 170 to 240°C, and more preferably, the reaction temperature is 180 to 220°C. Depending on the system used, the reaction is carried out under ultra-high pressure or atmospheric pressure.
[0058] In this invention, the chain extension reaction can be carried out in an extruder, a continuous kneader (List reactor), or a static mixer. The extruder may be a single-screw or twin-screw extruder. The static mixer can use SMR, SMX, or SMXL components, or a combination thereof. Examples of List reactors include single-screw DISCOTHERM B, twin-screw CRP, or ORP reactors. Preferably, the chain extension reaction is carried out in an extruder, with a residence time of 2 to 15 minutes, more preferably 4 to 12 minutes.
[0059] In the present invention, the aliphatic polyester can also be produced by reacting succinic acid and / or a succinic acid derivative with 1,4-butanediol in step (1) to obtain two types of esterified products, and then subjecting the two types of esterified products to subsequent prepolymerization reactions, polycondensation reactions, and optional chain extension reactions.
[0060] For example, the manufacturing method specifically includes the following steps:
[0061] Step (1-1): Succinic acid and / or succinic acid derivatives, 1,4-butanediol, and a branching agent are reacted for 2 to 6 hours under conditions of a temperature of 150 to 195°C and a pressure of 0.7 to 1.1 bar to obtain esterification product A having a carboxyl content of 320 to 480 mol / t.
[0062] Step (1-2): Sebacic acid and / or a sebacic acid derivative is reacted with 1,4-butanediol at a temperature of 180-220°C and a pressure of 0.6-1.1 bar for 2-6 hours to obtain esterification product B with a carboxyl content of 240-400 mol / t. Then, esterification product A and esterification product B are mixed and subjected to prepolymerization, polycondensation, and optional chain extension reactions. Here, the conditions for the prepolymerization, polycondensation, and optional chain extension reactions are selected from the same range as in Step (2), Step (3), and the chain extension reaction described above.
[0063] In the present invention, the origin of succinic acid and / or succinic acid derivatives is not particularly limited, and may be bio-derived succinic acid and / or succinic acid derivatives (i.e., the raw material for production is a biomass resource), or petroleum-derived succinic acid and / or succinic acid derivatives (i.e., the raw material for production is a petroleum resource).
[0064] In a second aspect, the present invention provides a polyester composition comprising the biodegradable aliphatic polyester described in the first aspect.
[0065] Preferably, the polyester composition further comprises at least one of a second polymer, a filler, or an auxiliary agent.
[0066] Preferably, the second polymer comprises at least one of the following: polylactic acid, polycaprolactone, polyhydroxyalkanoate, aliphatic polycarbonate, or aliphatic-aromatic polyester (e.g., polybutylene (adipate / terephthalate), polybutylene (terephthalate / adipate), etc.).
[0067] In this invention, in accordance with standard ISO 1133-2-2012, the melt flow rate of the second polymer is 0.5 to 50 g / 10 min under conditions of 190°C and 2.16 kg.
[0068] Preferably, the filler includes an inorganic filler and / or an organic filler.
[0069] In the present invention, the organic filler includes, but is not limited to, starch and / or cellulose, and the starch can be used in allosteric or gelled form. The starch may represent a continuous phase or a dispersed phase, or it may be in a cocontinuous form. The inorganic filler includes, but is not limited to, at least one of talc powder, calcium carbonate, and montmorillonite.
[0070] In conventional technology, it is common to reduce the filler content in the polyester composition to improve the heat seal strength of packaging bags, but reducing the amount of filler leads to an increase in material costs. On the other hand, the aliphatic polyester and polyester composition filled with the filler of the present invention can not only improve the heat seal strength of packaging bags but also reduce material costs.
[0071] In the present invention, the auxiliary agent can be added according to actual needs and includes, but is not limited to, compatibilizers, antioxidants, lubricants, and mold release agents. The compatibilizer includes, but is not limited to, maleic anhydride grafted polyethylene, maleic anhydride grafted polyolefin elastomer, maleic anhydride grafted styrene-acrylonitrile copolymer, etc. The antioxidant includes, but is not limited to, any one of antioxidant 1010, antioxidant 1076, antioxidant 168, antioxidant 164, antioxidant DLTP, or antioxidant TPP. The lubricant includes, but is not limited to, at least one of esters (e.g., polyethylene glycol ester, polyol ester), montanate, ethylene bis-stearamide, or polyethylene wax. The aforementioned release agent includes, but is not limited to, at least one of the following: an inorganic release agent (e.g., talc powder, mica powder, clay, etc.), an organic release agent (e.g., fatty acids, paraffin, glycerin, petrolatum, etc.), or a polymeric release agent (e.g., silicone oil, polyethylene glycol, low molecular weight polyethylene, etc.).
[0072] As a preferred technical solution of the present invention, the polyester composition comprises, by weight, 50 to 70 parts by weight of the biodegradable aliphatic polyester described in the first embodiment (for example, 50, 55, 60, 65, 70 parts, or in any range between the above numbers, but preferably 52 to 68 parts, more preferably 58 to 66 parts) and 4 to 20 parts by weight of the second polymer (for example, 4, 6, 8, 10, 12, 14, 16, 18, 20 parts, or in any range between the above numbers). It comprises a range (but preferably 4.5 to 10.5 parts), 15 to 35 parts of filler (for example, 15, 16, 18, 20, 22, 24, 25, 26, 28, 30, 32, 34, 35 parts, or any range between the above numbers, but preferably 17 to 27 parts), and 0 to 15 parts of auxiliary agent (for example, 1, 2, 4, 6, 8, 10, 12, 14, 15 parts, or any range between the above numbers).
[0073] In the present invention, the method for producing the polyester composition includes the steps of mixing a biodegradable aliphatic polyester, a second polymer, a filler, and an optional auxiliary agent, and extruding the mixture to obtain the polyester composition, wherein the extruder includes a reaction extruder, which may be a single-screw extruder, a twin-screw extruder, or a multi-screw extruder, the extrusion temperature is 140 to 220°C, and the screw rotation speed during extrusion is 200 to 500 rpm.
[0074] In a third aspect, the present invention provides a packaging bag, the raw material for manufacturing the packaging bag comprising the aliphatic polyester described in the first aspect or the polyester composition described in the second aspect.
[0075] In the present invention, other substances, such as colorants, may be added as necessary to the raw materials for manufacturing the packaging bag.
[0076] Preferably, the heat seal strength of the packaging bag is ≥15N / 15mm, more preferably ≥17.5N / 15mm, and most preferably ≥21N / 15mm.
[0077] In this invention, the heat seal strength of the packaging bag is determined by adjusting the packaging bag, which was obtained by inflating an aliphatic polyester at a set temperature of 140°C, by leaving it standing for 24 hours under conditions of 25±5°C and 55±5% humidity, and measuring it according to the standard QB / T 2358-1998. Specifically, in the heat seal process, the heat seal temperature is 100~130°C, the heat seal time is 1~5s, and the heat seal pressure is 200~400kPa.
[0078] In this invention, the packaging bag includes shopping bags, delivery bags, bags for fruits and vegetables, and the like.
[0079] The aliphatic polyester, polyester composition, and packaging film produced therefrom of the present invention are all biodegradable.
[0080] In this invention, a substance or mixture of substances is considered to have the characteristic of "biodegradability" if it exhibits a biodegradability rate of at least 90%, as defined in DIN EN 13432.
[0081] According to DIN EN 13432, the composting process involves introducing CO2-free air into the maturing compost and subjecting it to specific temperature treatments. Here, biodegradability is defined as the biodegradation rate, expressed as the ratio of the net amount of CO2 released from the sample (minus the amount of CO2 released from compost without the sample) to the maximum amount of CO2 that the sample can release (calculated from the carbon content in the sample). Biodegradable polyesters and biodegradable polyester compositions typically show clear signs of decomposition, such as fungal growth, dissolution, and perforation, within just a few days after composting.
[0082] Other methods for determining biodegradability are also described in ASTM D5338 and ASTM D6400.
[0083] The numerical range described in this invention includes not only the point values listed above, but also all point values within the numerical range not listed above. Due to space limitations and for the sake of brevity, this invention does not exhaustively list all specific point values included in the range. [Effects of the Invention]
[0084] Compared to conventional technology, the beneficial effects of the present invention are as follows:
[0085] The aliphatic polyester according to the present invention can have its heat seal strength improved by controlling the mole fractions of succinic acid residues and sebacic acid residues within a specific range, introducing branching agent residues, and controlling the content of branching agent residues within a specific range. As a result, packaging bags made from aliphatic polyester also have high heat seal strength, avoiding problems such as the edges of the packaging bags bursting or the bottoms being penetrated, and improving production efficiency. [Modes for carrying out the invention]
[0086] The technical solutions of the present invention will be further described below through specific examples. Those skilled in the art will understand that the examples described are merely to aid in understanding the present invention and should not be construed as particularly limiting the invention. In this invention, all materials used can be purchased commercially or prepared using conventional methods. Unless otherwise specified, the materials used in this invention are as follows:
[0087] 1,4-Butanediol: Purchased from Xinjiang MarkorChem Co., Ltd. Succinic acid: Purchased from Shandong Lanzian Biotechnology Co., Ltd. Sebacic acid: Purchased from Hengshui Jinghua Chemical Co., Ltd. Glycerin, pentaerythritol, and tartaric acid: all purchased from Aladdin. Tetrabutyl titanate: Purchased from Jianyi Chemical Import & Export Co., Ltd. In this invention, the methods for testing the molecular weight distribution coefficient, melt flow rate, carboxyl content, mole fractions of succinic acid residues and sebacic acid residues in aliphatic polyester, and mass fraction of branching agent residues are as follows.
[0088] 1. Molecular weight distribution coefficient: This is tested using gel permeation chromatography (GPC). Specifically, a chromatography system is used with three tandem columns (particle size 5 μm, porosity 500 Å, 1000 Å, and 10000 Å, respectively) and a refractive index detector. At 40°C, chloroform is used as the eluent (elution flow rate 1 mL / min), and polystyrene is used as the standard substance to measure Mw and Mn. The molecular weight distribution coefficient is calculated as Mw / Mn. The instrument model used is a Waters 1515GPC. The sample is prepared by directly dissolving an aliphatic polyester in chromatography-grade THF to prepare a 1 mg / mL solution for testing.
[0089] 2. Melt flow rate: Tested in accordance with standard ISO 1133-2-2012 under conditions of 190°C and 2.16 kg.
[0090] 3. Carboxylate content: This is performed in reference to standard GB / T 32366-2015. Specifically, it is done as follows: Dissolve 1 g of the sample in 50 mL of a mixed solvent of phenol and chloroform (volume ratio 2:3), use a 0.01 mol / L potassium hydroxide ethanol solution as the standard titration solution, and use a 0.2% bromophenol blue solution as the indicator. Perform a blank test based on the above test method for the carboxylate content of the sample. Test the sample twice in parallel, and the difference between the two test results must be 2 mol / t or less. The final result is the average of the two test results.
[0091] 4. Mole fraction: 1The sample is tested by 1H NMR. Specifically, 20 mg of the aliphatic polyester sample is dissolved in 0.6 mL of deuterated chloroform, and then the sample is analyzed at room temperature using a Bruker AV 500 NMR spectrometer. 1 1H NMR is measured. Characteristic chemical schiff peaks of succinic acid residues and sebacic acid residues (the characteristic chemical schiff of succinic acid residues is approximately 2.63 ppm, representing the four hydrogen atoms on the two methylene-CH2-CH2- in succinic acid; the characteristic chemical schiff of sebacic acid residues is approximately 1.30 ppm, representing the eight hydrogen atoms on the four methylene-CH2-CH2-CH2- in the center of sebacic acid) are integrated, and the mole fractions of succinic acid residues and sebacic acid residues, respectively, are obtained from the ratio of peak areas, assuming the total mole fraction of succinic acid residues and sebacic acid residues in the aliphatic polyester is 100 mol%. For example, if the integral area of succinic acid residues is I1 and the integral area of sebacic acid residues is I2, then the mole fraction of succinic acid residues in the aliphatic polyester, when the total mole fraction of succinic acid residues and sebacic acid residues in the aliphatic polyester is 100 mol%, is I1 / (I1+I2)×100%.
[0092] 5. Mass fraction of branching agent residues in aliphatic polyester: This is tested using the LC-MS method. Specifically, 0.5 to 1.5 g of the sample is added to a three-necked flask, 30 ml of 1 mol / L potassium hydroxide ethanol solution is added, and alkaline hydrolysis is carried out under reflux until the aliphatic polyester is completely hydrolyzed. After cooling, the sample is vacuum filtered, the filtrate is neutralized with concentrated hydrochloric acid, dried over anhydrous sodium sulfate, and filtered again. The filtrate is subjected to LC-MS to qualitatively and quantitatively analyze the branching agent residues. Examples 1-17, Comparative Examples 1-5
[0093] Examples 1-17 and Comparative Examples 1-5 each provide aliphatic polyesters. The composition of dibasic acid residues, the specific types and content of branching agent residues of the aliphatic polyesters are shown in Table 1. The content of branching agent residues is based on 100 wt% of the mass of the aliphatic polyester. The molecular weight distribution coefficient, melt flow rate, and carboxyl content of the aliphatic polyesters are also shown in Table 1.
[0094] The methods for producing the aliphatic polyesters obtained in Examples 1-17 and Comparative Examples 1-5 are as follows. Example 1
[0095] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1) 30.3 kg of succinic acid, 6.9 kg of sebacic acid, 35 kg of 1,4-butanediol, and 78 g of glycerin were physically mixed. After mixing was complete, the mixture was transferred to a 200 L esterification reactor and esterified for 5 hours at a temperature of 190 °C and a pressure of 1.1 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 24 g of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 80 min at a temperature of 243°C and a pressure of 0.60 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to polycondensation reaction for 110 minutes at a temperature of 245°C and a pressure of 1.2 mbar to obtain the aliphatic polyester. Example 2
[0096] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1) 25.8 kg of succinic acid, 11.4 kg of sebacic acid, 35 kg of 1,4-butanediol, and 78 g of glycerin were physically mixed. After mixing was complete, the mixture was transferred to a 200 L esterification reactor and esterified for 5 hours at a temperature of 190 °C and a pressure of 1.0 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 26 g of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 95 min at a temperature of 242°C and a pressure of 0.45 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to polycondensation reaction for 95 minutes at a temperature of 243°C and a pressure of 1.0 mbar to obtain the aliphatic polyester. Example 3
[0097] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1) 23.6 kg of succinic acid, 13.6 kg of sebacic acid, 35 kg of 1,4-butanediol, and 80 g of glycerin were physically mixed. After mixing was complete, the mixture was transferred to a 200 L esterification reactor and esterified for 4 hours at a temperature of 180 °C and a pressure of 0.8 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 27 g of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 90 min at a temperature of 244°C and a pressure of 0.52 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to polycondensation reaction for 100 minutes at a temperature of 245°C and a pressure of 1.1 mbar to obtain the aliphatic polyester. Example 4
[0098] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1) 22.5 kg of succinic acid, 14.7 kg of sebacic acid, 35 kg of 1,4-butanediol, and 76 g of glycerin were physically mixed. After mixing was complete, the mixture was transferred to a 200 L esterification reactor and esterified for 4 hours at a temperature of 180 °C and a pressure of 1.0 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 24 g of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 90 min at a temperature of 241°C and a pressure of 0.70 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to polycondensation reaction for 100 minutes at a temperature of 243°C and a pressure of 1.1 mbar to obtain the aliphatic polyester. Examples 5 to 10
[0099] The methods for producing the aliphatic polyesters described above are provided. The differences from Example 3 are as follows: The content and type of branching agent differed, and in the production methods of Examples 5 to 10, the added mass of branching agent was 68.0g, 85.0g, 55.0g, 110.0g, 80.0g, and 80.0g, respectively. The remaining raw materials, amounts used, and production methods were all the same as in Example 3. Example 11
[0100] A method for producing the aliphatic polyester is provided. The difference from Example 3 is that step (1) includes the following steps. (1-1) 23.6 kg of succinic acid, 25 kg of 1,4-butanediol, and 80 g of glycerin were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 4 hours at a temperature of 160°C and a pressure of 1.0 bar to obtain esterification product A. (1-2) 13.6 kg of sebacic acid and 10 kg of 1,4-butanediol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 4 hours at a temperature of 200°C and a pressure of 0.9 bar to obtain esterification product B. After mixing esterification product A and esterification product B, steps (2) and (3) were carried out. The remaining raw materials, steps, and manufacturing methods were all the same as in Example 3. Example 12
[0101] A method for producing the aliphatic polyester is provided. The differences from Example 11 are as follows. (1-1) 23.6 kg of succinic acid, 25 kg of 1,4-butanediol, and 80 g of glycerin were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 5 hours at a temperature of 180°C and a pressure of 1.0 bar to obtain esterification product A. (1-2) 13.6 kg of sebacic acid and 10 kg of 1,4-butanediol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 4 hours at a temperature of 210°C and a pressure of 1.0 bar to obtain esterification product B. (2) The esterification product A obtained in step (1-1) and the esterification product B obtained in step (1-2) were transferred to a vertical reactor with a stirring function, 27 g of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 85 min at a temperature of 240°C and a pressure of 0.65 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 50 minutes at a temperature of 242°C and a pressure of 1.4 mbar to obtain the polycondensation product. (4) The polycondensation product obtained in step (3) and hexamethylene diisocyanate (content: 0.28 wt% of the mass of the polycondensation product) were extruded in a reaction extruder at a temperature of 210°C, with a residence time of 8 minutes, to obtain the aliphatic polyester. Example 13
[0102] A method for producing the aliphatic polyester is provided. The differences from Example 11 are as follows. (1-1) 23.6 kg of succinic acid, 25 kg of 1,4-butanediol, and 32 g of glycerin were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 3 hours at a temperature of 170°C and a pressure of 1.0 bar to obtain esterification product A. (1-2) 13.6 kg of sebacic acid, 10 kg of 1,4-butanediol, and 48 g of glycerin were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 3 hours at a temperature of 190°C and a pressure of 1.0 bar to obtain esterification product B. After mixing esterification product A and esterification product B, steps (2) and (3) were carried out. The remaining raw materials, amounts used, and manufacturing methods were all the same as in Example 11. Example 14
[0103] A method for producing the aliphatic polyester is provided. The differences from Example 3 are as follows: In step (3), the prepolymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 110 minutes at a temperature of 248°C and a pressure of 1.1 mbar to obtain the aliphatic polyester. The remaining raw materials, amounts used, and manufacturing method were all the same as in Example 3. Example 15
[0104] A method for producing the aliphatic polyester is provided. The differences from Example 3 are as follows: In step (3), the prepolymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 58 minutes at a temperature of 245°C and a pressure of 1.3 mbar to obtain the aliphatic polyester. The remaining raw materials, amounts used, and manufacturing method were all the same as in Example 3. Example 16
[0105] A method for producing the aliphatic polyester is provided. The differences from Example 3 are as follows: In step (3), the prepolymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 45 minutes at a temperature of 240°C and a pressure of 1.4 mbar to obtain a polycondensation product. Step (4) further includes, after the polycondensation reaction, extruding the obtained polycondensation product with hexamethylene diisocyanate (content: 0.34 wt% of the mass of the polycondensation product) in a reaction extruder at a temperature of 200°C, with a residence time of 10 min, to obtain the aliphatic polyester. The remaining raw materials, amounts used, and manufacturing method were all the same as in Example 3. Example 17
[0106] A method for producing the aliphatic polyester is provided. The differences from Example 3 are as follows: In step (3), the prepolymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 50 minutes at a temperature of 242°C and a pressure of 1.4 mbar to obtain a polycondensation product. Step (4) further includes, after the polycondensation reaction, extruding the obtained polycondensation product and hexamethylene diisocyanate (content: 0.36 wt% of the mass of the polycondensation product) in a reaction extruder at a temperature of 210°C, with a residence time of 7 minutes, to obtain the aliphatic polyester. The remaining raw materials, amounts used, and manufacturing method were all the same as in Example 3. Comparative Example 1
[0107] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1) 32 kg of succinic acid, 5.2 kg of sebacic acid, 35 kg of 1,4-butanediol, and 80 g of glycerin were physically mixed. After mixing was complete, the mixture was transferred to a 200 L esterification reactor and esterified for 5 hours at a temperature of 190 °C and a pressure of 1.1 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 27 g of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 110 min at a temperature of 243°C and a pressure of 0.60 bar to obtain the prepolymerization product. (3) The prepolymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to polycondensation reaction for 100 minutes at a temperature of 245°C and a pressure of 1.2 mbar to obtain the aliphatic polyester. Comparative Example 2
[0108] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1) 20.9 kg of succinic acid, 16.3 kg of sebacic acid, 35 kg of 1,4-butanediol, and 80 g of glycerin were physically mixed. After mixing was complete, the mixture was transferred to a 200 L esterification reactor and esterified for 4 hours at a temperature of 180 °C and a pressure of 1.0 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 27 g of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 90 min at a temperature of 241°C and a pressure of 0.70 bar to obtain the prepolymerization product. (3) The prepolymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to polycondensation reaction for 100 minutes at a temperature of 245°C and a pressure of 1.2 mbar to obtain the aliphatic polyester. Comparative Example 3
[0109] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1) 23.6 kg of succinic acid, 13.6 kg of sebacic acid, 35 kg of 1,4-butanediol, and 147 g of glycerin were physically mixed. After mixing was complete, the mixture was transferred to a 200 L esterification reactor and esterified for 5 hours at a temperature of 190 °C and a pressure of 1.1 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 24 g of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 100 min at a temperature of 240°C and a pressure of 0.50 bar to obtain the prepolymerization product. (3) The prepolymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to polycondensation reaction for 90 minutes at a temperature of 242°C and a pressure of 1.4 mbar to obtain the aliphatic polyester. Comparative Example 4
[0110] A method for producing the aliphatic polyester is provided. The difference from Example 3 is the glycerin content. The remaining raw materials, amounts used, and manufacturing method were all the same as in Example 3. Comparative Example 5
[0111] A method for producing the aliphatic polyester is provided. The difference from Example 3 is that glycerin is not used. The remaining raw materials, amounts used, and manufacturing method were all the same as in Example 3.
[0112] [Table 1] Application Examples 1-17, Comparative Application Examples 1-5
[0113] Application Examples 1-17 and Comparative Application Examples 1-5 each provide polyester compositions. The polyester composition comprises, by weight, 63 parts aliphatic polyester, 4 parts polylactic acid, 25 parts starch, 4 parts glycerol, 3 parts water, and 1 part other additive (0.5 parts of a composite antioxidant consisting of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1, and 0.5 parts of ethylenebisstearate amide, which is a lubricant). The aliphatic polyester is provided in Examples 1-17 and Comparative Examples 1-5, respectively. The method for producing the polyester composition includes mixing each component according to the blending amounts, adding them to a twin-screw extruder (aspect ratio 48:1, diameter 40 mm), melt mixing, and extrusion granulation. The extrusion temperatures were as follows: Zone 1 120°C, Zone 2 160°C, Zones 3-9 180°C, Zone 10 170°C, Zone 11 170°C, die head 190°C, screw rotation speed 380 rpm, and vacuum -0.60 kg / cm². 2 The polyester composition was obtained. Here, the starch was purchased from Shandong Shouguang Juneng Jinyu Mi Development Co., Ltd. Polylactic acid (PLA, KB600 NF30) was obtained from Zhuhai Jin Generating Materials Co., Ltd. Performance testing
[0114] Polyester compositions containing aliphatic polyesters obtained in Examples 1-17 and Comparative Examples 1-5 were inflated under the following conditions to obtain packaging bags. The heat seal strength of the packaging bags was tested. The heat sealing process involved a heat sealing temperature of 115°C, a heat sealing time of 3 seconds, and a heat sealing pressure of 300 kPa.
[0115] The screw aspect ratio is 32:1, a spiral flow type die head is used, the air ring is a double outlet air ring, the inflation processing temperature is set to 140°C, the blow-up ratio is 3.5, and the inflation film thickness is 25±2μm.
[0116] The samples were left standing for 24 hours under conditions of 25±5℃ and 55±5% humidity, and a heat seal strength test was performed according to standard QB / T 2358-1998.
[0117] The specific test results are shown in Table 2.
[0118] [Table 2]
[0119] As can be seen from Table 2, the biodegradable aliphatic polyester of the present invention can be modified by adjusting the composition ratio of succinic acid residues and sebaciic acid residues in polybutylene succinate sebacate, which is a biodegradable polyester, and by introducing branching agent residues and adjusting the content of branching agent residues to a specific range, thereby significantly improving the heat seal strength of the packaging bag containing the biodegradable polyester. The heat seal strength of the resulting packaging bag is ≥15N / 15mm.
[0120] The specific embodiments described above further illustrate the object, technical solution, and beneficial effects of the present invention. These are merely specific embodiments of the present invention and do not limit it. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are also covered by the present invention.
Claims
1. An aliphatic polyester comprising a dibasic acid residue, a diol residue, and a branching agent residue, The aforementioned dibasic acid residue is, as a residue, a1): Based on the total mole fraction of a1) and a2) of 100 mol%, 71-89 mol% succinic acid residues, a2): Based on the total mole fraction of a1) and a2), it contains 11 to 29 mol% of sebaciate residues, The aforementioned diol residue is selected from at least a dibasic acid residue and an equimolar amount of a 1,4-butanediol residue. The aforementioned branching agent residues are derived from branching agents having ≥ 3 functional groups. An aliphatic polyester characterized in that the total mass of the aliphatic polyester is 100 wt%, and the mass fraction of the branching agent residue is 0.09 to 0.22 wt%.
2. The aforementioned dibasic acid residue is, as a residue, a1): Based on the total mole fraction of a1) and a2) at 100 mol%, 74-83 mol% succinic acid residues, a2): The aliphatic polyester according to claim 1, characterized in that it contains 17 to 26 mol% of sebaciate residues based on a total mole fraction of 100 mol% of a1) and a2).
3. The aliphatic polyester according to claim 1, characterized in that the total mass of the aliphatic polyester is 100 wt%, and the mass fraction of the branching agent residue is 0.11 to 0.17 wt%.
4. The molecular structure of the branching agent includes at least one of hydroxy, carboxy, or acid anhydride. Preferably, the branching agent comprises at least one of a polyol, a polybasic acid, a polyolic acid, or a polybasic acid anhydride, and more preferably a polyol. Preferably, the polyol comprises at least one of trimethylolpropane, trimethylolethane, pentaerythritol, polyethertriol, or glycerin. Preferably, the polybasic acid comprises at least one of trimesic acid, trimellitic acid, or pyromellitic acid. Preferably, the polyol acid comprises at least one of tartaric acid, citric acid, or malic acid. Preferably, the aliphatic polyester according to claim 1, wherein the polybasic acid anhydride comprises trimellitic anhydride and / or pyromellitic dianhydride.
5. The molecular weight distribution coefficient of the aliphatic polyester is 1.3 to 2.8, preferably 1.5 to 2.
5. Preferably, under conditions of 190°C and 2.16 kg, the melt flow rate of the aliphatic polyester is 1.2 to 10 g / 10 min, and more preferably, the melt flow rate is 2.2 to 6 g / 10 min. Preferably, the aliphatic polyester according to claim 1, characterized in that the carboxyl content of the aliphatic polyester is <50 mol / t.
6. A polyester composition, The polyester composition is characterized by comprising the aliphatic polyester described in any one of claims 1 to 5.
7. The polyester composition further comprises at least one of a second polymer, a filler, or an auxiliary agent. Preferably, the second polymer comprises at least one of polylactic acid, polycaprolactone, polyhydroxyalkanoate, aliphatic polycarbonate, or aliphatic-aromatic polyester. Preferably, the polyester composition according to claim 6 is characterized in that the filler includes an inorganic filler and / or an organic filler.
8. The polyester composition according to claim 6, characterized in that the polyester composition comprises, by weight, 50 to 70 parts by aliphatic polyester, 4 to 20 parts by a second polymer, 15 to 35 parts by a filler, and 0 to 15 parts by an auxiliary agent.
9. A packaging bag characterized in that the raw materials for manufacturing the packaging bag include the aliphatic polyester described in claim 1.
10. The packaging bag according to claim 9, characterized in that the heat seal strength of the packaging bag is ≥ 15 N / 15 mm.
